STRATEGI PENGEMBANGAN KAWASAN AGROPOLITAN BERBASIS TANAMAN PANGAN DI KOTA PADANG (Agropolitan Development Strategy Based on Food Crops in Padang City) - Ilham Martadona; Yeti Lis Purnamadewi; Mukhamad Najib (TATALOKA, 2014)
The role of Agricultural sector isn't only to ensure food supplies but also as an income generating through export activities. Padang is potentially developed to modern agriculture due to vast number of agriculture land.  Base on regulation No.18 of 2004 on RPJP and Regulation No.9 of 2009 on RPJM, Padang is declared as Agropolitan area. The Agropolitan concept is expected to increase agriculture-based development, because the GDP share of agriculture is relatively small. This study aims are to  analyze a basic food crops, 2) to choose the region which will develop as agropolitan area base on availability of facilities and infrastructure in that region and 3) to formulate development strategies of agropolitan area. The analysis of LQ indicate rice crop as the basic commodity with the LQ greater than one. Skalogram analysis and diamond porter show that Sub District Kuranji is potentially developed as a growth center in the Agropolitan Area because it has the most complete facilities and infrastructure. In this research the development strategies are to develop agricultural infrastructure (sub terminal of agribusiness) and institutional strengthening of capital institution.